PENGARUH KOMPETENSI PROFESIONAL GURU, MOTIVASI KERJA DAN KONSEP DIRI TERHADAP KINERJA GURU DI MADRASAH ALIYAH NEGERI KABUPATEN KAMPAR - Faizin Faizin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
Teachers are a very dominant factor and most important in formal education, therefore teachers are often used asrole models and even become self-identification figures for students. The concept of self is an important part inevery conversation about human personality. This study aims to determine the planning and implementationprogram acceleration in madrasah aliyah negeri in Kabupaten Kampar This research method is descriptive methodwith quantitative approach. The unit of analysis in this study is the Influence of professional teacher competence,work motivation and self concept on teacher performance at madrasah aliyah negeri in Kabupaten Kampar. Afterthe data were analyzed, it was concluded: 1) the influence of professional teacher competence, work motivation andself concept on teacher performance In madrasah aliyah negeri in Kabupaten Kampar is with a percentage of63.83% there is a significant influence between the performance of madrasah teachers to guidance paedagogikteacher competence with the effect of 0.489. Based on the above conclusions, it is known that the professionalteacher competence, work motivation and self concept in the learning process determine the professionalism ofteachers in learning can increase and can lift the quality of teachers through the performance of madrasahteachers.